ACTN3 gene and sports performance: a candidate gene to success in short and long duration events. - Leonardo Alves Pasqua; Guilherme Giannini Artioli; Flávio de Oliveira Pires; Rômulo Cássio de Moraes Bertuzzi (Universidade Federal de Santa Catarina, 2011)
The aim of the present study was to review the evidence on the relationship between the R577X polymorphism of the ACTN3 gene and sports performance. The Pubmed database was searched using ACTN3 gene AND sports performance as keywords. The ACTN3 gene encodes a muscle-specific protein, called α-actinin-3, which is only present in type II fibers. Most studies have demonstrated a relationship between the presence of α-actinin-3 and the ability of muscle to generate force. However, recent studies suggest that the absence of the functional form of this protein may regulate substrate utilization during exercise, giving priority to oxidative metabolism, sparing muscle glycogen, and improving performance in long-duration events. Nevertheless, further studies involving humans are needed to better understand the metabolic role of this protein.